Pengaruh Kepemimpinan, Komunikasi, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Telkomsel Region Kalimantan - Dzaky Firdaus Sarujih, Muhammad; Hadiyatno, Didik; Yuliani, Tutik (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
This study aims to examine and analyze the influence of leadership, communication, and work environment on job satisfaction of Telkomsel Kalimantan Region employees. This study uses a quantitative approach. The sampling technique uses purposive sampling technique with permanent employee criteria with a sample of 115 respondents. Data collection methods are carried out through interviews, documentation, and questionnaire distribution. Data analysis uses SmartPLS software. The results of the study indicate that: leadership and work environment influence job satisfaction of Telkomsel Kalimantan Region employees and communication does not influence job satisfaction of Telkomsel Kalimantan Region employees